PREDICTIVE DESIGN OF THE F-POLICY MARKOVIAN QUEUE - Al-Matar, Najeeb; Tadj, Lotfi (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
We consider in this paper the queueing model under the policy. In this system, customers are denied entry when the system is full, until the queue size drops to the level , following the departure of served customers. To start the admission of customers again, a startup job is required for the server. Since the goal of the F-policy is to gain control over the system, we propose an approach that selects the optimal system parameters. Numerical examples validate the theoretical results obtained.